Pediatric kidney transplant recipients are at an increased risk for dysbiosis - Yılmaz, Gizem; Saygılı, Seha; Ağbaş, Ayşe; Karabağ Yılmaz, Esra; Variş, Ahmet; Canpolat, Nur (Frontiers in Microbiology, 2025)
IntroductionThis study aimed to compare the gut microbiota composition in pediatric kidney transplant (KTx) recipient with that of healthy children.MethodsThis cross-sectional observational study included 30 pediatric KTx recipients aged between 7 and 21 years and 25 healthy children. The gut microbiota was assessed using 16S rRNA gene sequencing, with alpha and beta diversity, as well as all statistical analyses, conducted using the Phyloseq library in the R programming language. Taxonomic profiles were evaluated with QIIME2, and differences in gut microbiota profiles were compared using linear discriminant analysis effect size (LEFSe) with an LDA threshold of >2 and p < 0.05.ResultsNo significant differences were found in alpha and beta diversity between the KTx recipients and healthy controls. However, KTx recipients exhibited significant alterations in microbiota composition, including higher relative abundances of Verrucomicrobiota at the phylum level, and Akkermansia and Neisseria at the genus level (p < 0.05 for all). Conversely, there was a decrease in bacterial genera belonging to the phylum Firmicutes. In addition, KTx recipients with a history of frequent urinary tract infections, diarrhea and reduced GFR showed significant increases in bacterial abundance (p < 0.05 for all).DiscussionPediatric KTx recipients demonstrated significant alterarions in gut microbiota composition, indicating dysbiosis. Further studies are needed to elucidate the cause-and-effect relationships of these changes and their impact on clinical consequencies and long-term prognosis.